Sex differences in muscle fatigue following isokinetic muscle contractions - Miguel Gomes (Nature Portfolio, 2021)
Abstract Muscle fatigue is a limiting factor of human performance. It is unclear whether sex-based differences in fatigability exist during dynamic exercise of varying velocities of contraction. We aimed at exploring sex differences in muscle fatigue elicited by maximal isokinetic muscle contractions performed at different angular velocities. Twenty-six healthy participants (13 men: 23.2 ± 1.5; 13 women: 21.9 ± 3.0 years) were tested for concentric knee-extension at slow, moderate and fast angular isokinetic velocity (60, 180 and 300º.s−1, respectively), on non-consecutive days. The impact of sex on fatigue resistance and consecutive recovery for each isokinetic condition was explored by calculating the percent change in maximal voluntary isometric contraction (MVIC) and in rate of torque development (RTD), from pre- to post-isokinetic exercise (30 repetitions). The isokinetic fatigue index was also determined. No sex differences were obtained in response to isokinetic contractions completed at 60º.s−1. After performing muscle contractions at 300º.s−1, women had a significantly greater loss in MVIC than men (− 18.4 ± 5.5 vs. − 12.9 ± 3.8%; p = 0.009) and larger decreases in work output during isokinetic exercise (− 34.2 ± 8.9 vs − 27.5 ± 10.6%; p = 0.017). Recovery of initial MVIC strength was greater for women post-exercise at 180º.s−1 (15.6 ± 4.1% vs. 6.7 ± 9.5; p = 0.003). No differences were found between sexes in any condition for RTD from pre- to post-fatigue. These results suggest the presence of a sexually dimorphic fatigability in response to dynamic (isokinetic) contractions favouring men at higher absolute velocities of contraction.